SOCIAL SUPPORT AND RELATIONSHIP WITH THE SELF-CONFIDENCE OF WHEELCHAIR BASKETBALL PLAYERS HANDICAPS - AL-SHAMMARI, ASSET. PROF. DR. FADEL KURDI; AL-JUBOuri, DR. AYMAN HANI; ABDULLAH, NIVYAN YASSER (Journal of Duhok University, 2019)
The research aims to identify the social support and its relationship with the self-confidence of wheelchair basketball players with special needs, the researchers hypothesized that there is a relationship between social support and self - confidence for wheelchair basketball players with special needs. The researchers used the descriptive method of surveying and correlation relationship. The researchers identified the research community of disabled basketball players in the province of Babylon and the number (20) players, and a sample of research where (15) players and randomly selected and also (5) players for the exploratory experiment. The researchers then came to the conclusions that most basketball players have social support and good self-confidence. There is a direct correlation between social support and self-confidence. Addresses the relationship between social support and self-confidence and some other psychological variables and the need to conduct a comparative study between the variables for a number of individual and different sports